Beat The Course of Impaired Water and Salt Metabolism in Patients with Heart Failure - Kenjayev Ruxidin Uroq o‘g‘li; Sharipov Davlat Ma’ruf o‘g‘li; Erqulov Ulug‘bek Urol o‘g‘li; Norboyev Mardon Berdiyevich (Scholars Digest Publishing, 2023)
The live weight of naked black-bred cattle is considered an important and main selection trait and reflects the level of development of the animals. The same can be said about the live weight of cows. For this purpose, we conducted studies of live weight and body size of domestic black ola cows.
Keywords: Golishtinated, cow, breed, black ola, live vase, lactation, constitution and milk.